EVALUASI KURIKULUM PEMBELAJARAN PAI DI SEKOLAH DAN MADRASAH: TELAAH PUSTAKA TERHADAP PARADIGMA DAN PRAKTIKNYA DI INDONESIA - Radjendra, Ryan; Agus Pahrudin; Agus Jatmiko; Koderi; Imam Syafei (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the Islamic Education curriculum and learning in schools and madrasahs through a library research approach. The review explores academic literature, books, and journal articles discussing paradigms, implementation, and the relevance of Islamic Education curricula within the context of modern education. The findings reveal that Indonesia’s Islamic Education curriculum continues to adapt to digital-era demands, yet faces challenges in integrating Islamic values with contemporary pedagogical approaches. The paper emphasizes the importance of reconstructing curricula based on spiritual values, digital literacy, and student character formation. Thus, this study contributes to enriching the discourse on developing adaptive, contextual, and character-oriented Islamic Education curricula.